Intimate Partner Violence and its Escalation Into Femicide. Frailty thy Name Is “Violence Against Women” - Zara, Georgia; Gino, Sarah (Frontiers in Psychology, 2018)
Violence against women is a disabler of dignity, liberty, and rights of the person, with murder being its extreme form for silencing the individual. Despite psycho-criminological research providing evidence that violence can happen across cultures, sexes, and societies, other findings show that some forms of violence i.e. Intimate Partner Violence (IPV), which involves more frequently women as victims, is not rare in contemporary society. The aim of this study is to analyze the violence against women, and how it escalates up to the point in which it aggravates into femicide. In order to carry out this study, data from both the Turin Archive of the Institute of Legal Medicine (1970-1997), and the Archive of the Central Morgue (1998-2016) were collected. The interest was to focus on those women who were killed in Turin, between 1970 and 2016, by a male with whom they were involved in a more or less intimate relationship (e.g. matrimonial, sexual, friendship, professional, etc.). Collateral information was also gathered from forensic files that reported sufficient details about the criminal events. The sample was composed of 275 women killed by violence in Turin, Italy, by 260 males. This research was based on two questions: Is murder the worst possible scenario of a long-lasting abusive relationship? Are we witnessing a shift in how violence now happens, becoming perhaps less striking than murder, but not less painful from the victim’s point of view? These findings show that escalation into femicide featured more likely within an intimate and affective relationship between victim and perpetrator; they also show that when the perpetrator knew the victim, it was more likely that an overkilling took place. When victims sustained multiple injuries that went beyond those necessary to cause their death, one is in front of an overkilling. These results also suggest that motives behind intimate partner femicide could account for a differential degree of violence, so that the longer and closer the relationship was between victim and perpetrator, the higher the risk of IPV escalating into femicide, and of femicide being executed with extreme and severe force.